The influence of core self-evaluations on determining blame for workplace errors: an ANOVA-attribution-model approach - Krome, Lesly R. (Kansas State University, 2013)
The current study examined attributions of blame for workplace errors through the lens of Kelley’s (1967) ANOVA model of attribution-making, which addresses the consensus, consistency, and distinctiveness of a behavior. Consensus and distinctiveness information were manipulated in the description of a workplace accident. It was expected that participants would make different attributions regarding the cause of the event due to these manipulations. This study further attempted to determine if an individual’s core self-evaluations (CSE) impact how she or he evaluates a workplace accident and attributes blame, either from the perspective of the employee who made the error or that of a co-worker. Because CSE are fundamental beliefs about an individual’s success, ability, and self-worth, they may contribute to how the individual attributes blame for a workplace accident. It was found that CSE were positively related to participants’ inclination to make internal attributions of blame for a workplace error. Contrary to expectations, manipulations of the consensus and distinctiveness of the workplace error did not moderate participants’ attributions of blame. Explanations for these findings are discussed, as are possible applications of this research.
Keywords: Core self-evaluations; Workplace errors; Attribution theory; ANOVA model; Psychology (0621)